1997
DOI: 10.1038/bjc.1997.533
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of hepatic prothymosin alpha, a novel marker for human hepatocellular carcinoma

Abstract: Summary Identification of gene products exclusively or abundantly expressed in cancer may yield novel tumour markers. We recently isolated a number of cDNA clones, including a-prothymosin, from rat hepatocellular carcinoma (HCC) using a subtraction-enhanced display technique. a-Prothymosin is involved in cell proliferation and is regulated by the oncogene c-myc in vitro. In the present study, we analysed a-prothymosin gene expression and its correlation with c-myc in patients with HCC, cirrhosis and adenoma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 23 publications
(24 reference statements)
2
41
0
2
Order By: Relevance
“…PTMA has been reported to be associated with cancer progression in the liver, lung, prostate, and bladder (28)(29)(30)(31). In this study, PTMA knockdown resulted in BC cell viability inhibition and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 60%
“…PTMA has been reported to be associated with cancer progression in the liver, lung, prostate, and bladder (28)(29)(30)(31). In this study, PTMA knockdown resulted in BC cell viability inhibition and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 60%
“…In situ hybridization revealed that overexpressed proT mRNA was restricted to neoplastic nodules in the hepatic tissue and to tumor cells invading blood vessels [44]. Thymosin 10 1983 42-44 Ubiquitous in man, mouse and rat, cytoplasm [19] In humans, high proT mRNA levels were correlated with those of c-myc in colon [45] and liver cancer [46] and N-myc in neuroblastoma [47] (Table 2). However, although lung cancer tissues showed similarly elevated proT mRNA expression, this was not paralleled by c-myc mRNA increase [48], indicating that simultaneous transcription of the two genes does not occur in all cancer types.…”
Section: The Dual-intracellular and Extracellular-role Of Protmentioning
confidence: 99%
“…ProTα was shown as a marker for breast cancer [68], hepatocarcinoma [69], and plasma levels of its derivative Tα 1 been proposed as a marker for the prognosis of lung cancer [70]. In ligand blotting assays, ProTα bound only to chromatin pools and nuclear fractions where histone H1 was present [71,72].…”
Section: Thymosin Family Members and Cell Cyclementioning
confidence: 99%
“…In the fission yeast Schizosaccharomyces pombe, the execution of Start requires the activity of the Cdc2 protein kinase and the Cdc10/Sct1 transcription complex. The loss of any of these genes leads to G1 arrest [69].…”
Section: Thymosin Family Members and Cell Cyclementioning
confidence: 99%